Expression characteristics of metabotropic glutamate receptor 4 in cochlear hair cells during early postnatal stages in mice - CHEN Zhiji; LIU Xuelai; ZHOU Xiaoqing (陆军军医大学学报)
‍Objective‍　‍To investigate the spatiotemporal expression pattern of metabotropic glutamate receptor 4 (mGluR4) in the mouse cochlear basilar membrane and its dynamic changes during postnatal development until hair cell synaptic maturation. Methods‍　‍Ten healthy 3-month-old C57BL/6L wild-type mice (5 males, 5 females, 25～35 g) were bred to obtain offspring. Cochlear samples from postnatal days 1~30 (P1~P30) were analyzed. Frequency-specific auditory brainstem response (ABR) thresholds were measured at 45.2, 32.0, 22.6, 16.0, 11.3, 8.0, 5.6, and 4.0 kHz in P12, P14, P16, P21, and P30 mice. Immunofluorescence assay combined with confocal laser scanning microscopy was used to scan cochlear whole-mount preparations. Spatiotemporal co-localization profiling of mGluR4 and synaptic markers Ctbp2 and Snap25 was observed, and quantitative comparisons of fluorescent puncta density were performed. Results‍　‍ABR testing revealed undifferentiated waveforms in all P12 mice, while 70% of P14 mice exhibited well-defined Wave I. In P14, P16, P21 and P30, mice undergoing ABR testing, 50% failed to exhibit ABR waveforms when stimulated by 45.2 kHz tones, and 87.5% showed no response to 32.0 kHz stimuli. Auditory response thresholds for other frequencies progressively decreased with increasing postnatal age. Immunolocalization demonstrated stronger mGluR4 expression in inner hair cells (IHCs) versus outer hair cells (OHCs). Distinct mGluR4 puncta were observed at IHC presynaptic active zones (co-localized with Snap25) as early as P11, but showed minimal overlap with CtBP2-labeled ribbons. Quantitative analysis revealed significantly higher mGluR4 puncta density at P30 compared to P14 synapses (P<0.05). Conclusion‍　‍Postnatal upregulation of mGluR4 at IHC synaptic regions correlates with functional maturation. These findings suggest mGluR4 may modulate vesicular exocytosis regulation and exert pharmacological inhibition on glutamate release, potentially influencing synaptic plasticity during auditory pathway refinement.